PHYSICAL - CHEMICAL AND BACTERIOLOGICAL ANALYSIS OF THE RIVER DRINI I BARDHE - Haxhibeqiri, Burim; Maloku, Faton; Brahushi, Ferdi (European Scientific Journal, ESJ, 2014)
Water quality in the River Drini i Bardhë is influenced by various factors. The main influence comes from urban leaks, discharges of pollutants from wastewater, as well as infiltration from agriculture, discharges from industries which perform their activities in the river basin of Drini i Bardhë. The purpose of this work is to provide data on water quality of river Drini i Bardhë , based on physical chemical and bacteriological monitoring form broad source of river until the end flow in Kosova. In this paper are analyses of physical chemical and bacteriological parameters in water of river Drini i Bardhë, such as temperature, specific conductivity, total hardness, dissolved oxygen, potassium permanganate value, turbidity, nitrites, ammonia, phosphates, iron, manganese as well as bacteriological parameters, such as total number of coliform bacteria in 100 ml, fecal originating coliform bacteria in 100 ml, the total number of aerobic mesophilic bacteria. Water samples were analyzed in physical chemical and bacteriological laboratory, with methods like volumetric method, atomic absorption method (AAS), spectrophotometric methods, etc. During this research parameters that were measured are physical chemical and bacteriological and they were presented in tables. They are considered important indicators in the river Drini i Bardhë and they indicate an elevated presence of all the parameters due to several tributary river inflow into the river Drini i Bardhë. In these statements of test results is given a general water quality of the river Drini i Bardhë relying on the based on chemical, physical and bacteriological contamination that show the quality of the river Drini i Bardhë as consequence of urban and, pollutant dischargers..